2019
DOI: 10.1007/s40789-019-0237-6
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory results of a 3rd generation roof bolter canopy air curtain for respirable coal mine dust control

Abstract: Testing was completed on an earlier roof bolter CAC that used slots to provide a perimeter airflow. NIOSH tested it due to its unique design that differed from canopies that provided uniform airflow. Based upon NIOSH recommendations from the earlier testing, a 3rd generation roof bolter CAC has been developed by J.H. Fletcher & Co. The changes to this CAC involve design modifications to the plenum outlets, using a single row of outlets on the perimeter and a different material for the plenum. This laboratory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…This supports the argument that the operators' reduced respirable dust exposures were influenced positively by the CAC. Similar control efficiencies were observed in the lab when testing this canopy design, supporting the results collected in the field (Reed et al 2017(Reed et al , 2019b.…”
Section: Or Right Bolter Concentration Bolter Middle Concentration ð2þsupporting
confidence: 82%
“…This supports the argument that the operators' reduced respirable dust exposures were influenced positively by the CAC. Similar control efficiencies were observed in the lab when testing this canopy design, supporting the results collected in the field (Reed et al 2017(Reed et al , 2019b.…”
Section: Or Right Bolter Concentration Bolter Middle Concentration ð2þsupporting
confidence: 82%
“…For measuring the air ow, this analysis included measuring the air ow across the plenum including at three different heights (25.4, 50.8, and 76.2 cm) below the CAC to determine how rapidly the air ow may decrease. Reed et al 2019 [14] demonstrated that the air ow and reductions in dust concentrations will start to decrease as one is farther from the CAC. Therefore, three distances below the CAC were measured to determine the location of the CAC in reference to the mine worker which provides protection from DPM.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…In order to increase its effectiveness, Fletcher re-designed the air canopy based upon recommendations from NIOSH to provide air ow over the entire canopy, using a staggered perimeter air ow design with a higher ow rate that prevented contaminated air from entering the CAC protection zone. Laboratory testing demonstrated that this change increased the reduction from 17-24% to approximately 50% [14]. Field testing the roof bolter CAC in underground coal mines with this design showed respirable dust reductions ranging from 3-60% [15].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In recent years, with the gradual improvements of mechanization and automation of the coal mine production in China, the dust-caused potential safety hazard and occupational health problems have become even more serious (Xu et al 2017;Reed et al 2019;Yao et al 2020). At the production site of coal mine, high-concentration dust reduces the productivity of miners, affects output and benefit of the coal mine, and leads to death of the miners who suffer from the pneumoconiosis that cannot be cured for a long period, or leads to coal dust explosion and major accidents (Fan et al 2018;Han et al 2020).…”
Section: Introductionmentioning
confidence: 99%